Field Measurement of PV Array Temperature for Tracking and Concentrating 1 k Wp Generators Installed in Malaysia - M. Effendy Ya’acob; H. Hizam; M. Amran M. Radzi; M. Z. A. A. Kadir (International Journal of Photoenergy)
The effect of temperature elements for PV array with tracking and concentrating features installed in the tropical ground condition is presented. The temperature segment covers ambient temperature and surface and bottom temperature for three types of PV generator systems, namely, Fixed Flat (FF), Tracking Flat (TF), and Concentrating PV (CPV) generators. The location of measuring the cell temperature, Tc for the PV module is still being debated by researchers with the issue of how much the cell temperature (Tc) is being affected by the surface temperature (Ts), bottom temperature (Tb), and surrounding temperature (Ta) furthermore when it is located in fluctuating weather conditions. In this study, ΔT is calculated based on the difference between surface temperature and bottom-side temperaturewhichever the highest recorded at site for different kinds of PV generator systems but using the same CEEG 95 W monocrystalline PV module. The study embraces the direct correlation of various temperature elements in tropical-based condition with ΔT values of 2.19°C for FF module, 2.22°C for TF module, and 2.72°C for CPV module. These values which reflect the different unique configurations are further analyzed using multiple linear regression (MLR) and analysis of variance (ANOVA) test for Tarray models. This study supports the continuous research in adapting PV technology for Malaysia.